Survey of Hospital Chargemaster Transparency - Arvisais-Anhalt, Simone; McDonald, Samuel; Park, Jason Y.; Kapinos, Kandice; Lehmann, Christoph U.; Basit, Mujeeb (Applied Clinical Informatics, 2021)
Background In January 2019, the Centers for Medicare & Medicaid Services (CMS) required hospitals to list their standard charges (chargemasters) publicly in an effort to increase price transparency in health care. Surveying hospital chargemasters may be informative to assess the implementation of this rule and its utility to consumers.Objective We aimed to compare hospital chargemaster data within a local hospital market where patients would reasonably try to shop or compare services.Methods We identified and aggregated Dallas County hospital chargemasters available in a database compatible format in May 2019. We manually examined a convenience sampling of 10 common laboratory tests, medications, and procedures.Results Thirteen hospital chargemasters were identified. Eleven hospitals had chargemasters available in a database compatible format (xlsx or csv). These 11 chargemasters were aggregated into a single file containing 155,576 chargeable items, prices, and descriptions. We observed heterogeneous names and descriptions of synonymous items across institutions, preventing automated comparisons. The examined items revealed a high variation in charges. The largest charge variation for laboratory tests examined included a 2,606% difference (partial thromboplastin time: $18.70–506.00), for medications an 18,617% difference (5-mg tablet of amlodipine: $0.23–43.05), and for procedures a 2,889% difference (circumcision: $252.00–7,532.10). One institution accounted for 27% of the lowest prices and another accounted for 60% of the highest prices.Conclusion Chargemaster data presentation varied among the hospitals surveyed, making automatic comparison impossible. Chargemaster data are difficult to interpret for health care decisions. Refining the minimum requirements for publishing chargemaster data could increase their utility.
Keywords: price transparency; chargemaster; health policy; Centers for Medicare & Medicaid Services; U.S.